Further Peripheral Vascular Dysfunction in Heart Failure Patients With a Continuous-Flow Left Ventricular Assist Device: The Role of Pulsatility - Witman, Melissa A H; Garten, Ryan S; Gifford, Jayson R; Groot, H Jonathan; Trinity, Joel D; Stehlik, Josef; Nativi, Jose N; Selzman, Craig H; Drakos, Stavros G; Richardson, Russell S (JACC. Heart failure, 2015)
Using flow-mediated vasodilation (FMD) and reactive hyperemia (RH), this study aimed to provide greater insight into left ventricular assist device (LVAD)-induced changes in peripheral vascular function. Peripheral endothelial function is recognized to be impaired in patients with heart failure with reduced ejection fraction (HFrEF), but the peripheral vascular effects of continuous-flow LVAD implantation, now used as either a bridge to transplantation or as a destination therapy, remain unclear. Sixty-eight subjects (13 New York Heart Association [NYHA] functional class II HFrEF patients, 19 NYHA functional class III/IV HFrEF patients, 20 NYHA functional class III/IV HFrEF patients post-LVAD implantation, and 16 healthy age-matched control subjects) underwent FMD and RH testing in the brachial artery with blood flow velocity, artery diameters, and pulsatility index (PI) assessed by ultrasound Doppler. PI was significantly lower in the LVAD group (2.0 ± 0.4) compared with both the HFrEF II (8.6 ± 0.8) and HFrEF III/IV (8.1 ± 0.9) patients, who, in turn, had significantly lower PI than the control subjects (12.8 ± 0.9). Likewise, LVAD %FMD/shear rate (0.09 ± 0.01 %Δ/s(-1)) was significantly reduced compared with all other groups (control subjects, 0.24 ± 0.03; HFrEF II, 0.17 ± 0.02; and HFrEF III/IV, 0.13 ± 0.02 %Δ/s(-1)), and %FMD/shear rate significantly correlated with PI (r = 0.45). RH was unremarkable across groups. Although central hemodynamics are improved in patients with HFrEF by a continuous-flow LVAD, peripheral vascular function is further compromised, which is likely due, at least in part, to the reduction in pulsatility that is a characteristic of such a mechanical assist device.